GAMBARAN INTERAKSI OBAT PADA PASIEN GAGAL JANTUNG KATEGORI GERIATRI JAMINAN BPJS DI KLINIK JANTUNG RUMAH SAKIT ISLAM JAKARTA CEMPAKA PUTIH PERIODE OKTOBER-DESEMBER 2018 - Siti Aisyah; Meiana Dwi Andini; Gunawan Hadi Saputra (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Heart failure is one of the diseases with the highest number of patients in Indonesia. Most of them are geriatric ages or 65-74 years old patients. At this age, the body phsyological functions are declined and other health problems appear such as cognitive disorder, body balance, vision and hearing disorder. Geriatric age patients need a variety of medicine in their treatment or called polypharmacy and it has a potential to cause drug interactions. Previously two studies on drug interactions in heart failure patients have been conducted with results are found drug interactions in both studies. In order to realize towards health services, the government build BPJS to ensure the health of all Indonesian people through JKN program and cooperate with many health facilities. Jakarta Islamic Hospital Cempaka Putih also cooperate with BPJS giving treatment for heart failure. Data on medical records from January to September 2018 showed that heart failure were in top 10 biggest diseases with 1.341 patients, 70% of them were BPJS guaranteed patients. This study aims to find out about the description of drug interactions on geriatric age heart failure patients with BPJS insurance at cardiac clinic of Jakarta Islamic Hospital Cempaka Putih in October-December period. This research is a retrospective descriptive-quantitative study with sampling technique used Nonprobability Sampling. The sample in this study amounted 134 sheets of recipes. The results showed that the drug interactions with major severity were 1,63%, moderate 93,67%, and minor 4,70%. The conclusion is that 98,51% of drug interactions were found.